A atuação da legislação ambiental na implementação de reservas legais: uma análise para a região central do estado de São Paulo no período de 35 anos (1983-2018) - Amorim, Lia Martucci de (Universidade Federal de São Carlos, 2019)
The compliance with the Environmental Legislation during the implementation of Legal Reserves for the territorial limits of 23 municipalities located in the Central Region of the State of São Paulo, over the period of 35 years, was analyzed. The analysis was based on the development of a georeferenced database of Legal Reserves numbers and areas, between 1983 and 2013, under Federal Law n° 4.771/1965, and between 2013 and 2018, associated with the implementation of Federal Law n° 12.651/2012 and of the Rural Environmental Registry. The inventory of Legal Reserves numbers and areas, for the period of 1983-2013, was obtained from the consultation of the Integrated Environmental Management System (SIGAM), used by the São Paulo State Secretariat of Infrastructure and Environment (SIMA) for management and administrative proceedings. For the period of 2013-2018, the data were obtained from the consultation of the digital database of the São Paulo State Rural Environmental Registry System (SiCAR-SP). Between 1983 and 2013, 854 Legal Reserves with a total extension of 54,950ha were implemented for the territorial boundaries of the 23 municipalities in the Central Region of the State of São Paulo. Between 2013 and 2018 (September), a total of 4,550 Legal Reserves were potentially identified, equivalent to a total area of 146,444ha. Over the 35-year period (1983-2018), the São Carlos municipality had the highest number of registrations (524) and total area (22,208.04ha), while the municipality of Águas de São Pedro presented the smallest total area (24.07ha) and number of records (02) of Legal Reserves. The spatial cumulative scenario of the total areas of Legal Reserves in 2018, for the municipalities in the study area, highlighted São Carlos (30%), Ibaté (30%) and Trabiju (52%) with the highest percentages of municipality area defined as Legal Reserve, i.e., the municipalities that displayed the highest compliance with the environmental legislation. On the other hand, the Itaju (3%), Jaú (7%) and Bariri (7%) municipalities presented scenarios that were critically compromised with regards to the deficit of protected area in rural properties, due to the lower percentages of agricultural areas potentially protected in the form of Legal Reserve. An effective indicator for the government to act in relation to the fragility or administrative failure of these municipalities to comply with the environmental legislation. Although not all areas declared as Legal Reserves in SiCAR in 2018 represent a real implemented scenario, a potential increase of 432% in the number and of 170% in the extension area (ha) of Legal Reserves was estimated to Central Region of the State of São Paulo, between 2013 and 2018. These results show a trajectory that points to the increase in the amount of native vegetation in the study area, especially in terms of the number and extent of legally protected areas configured as Legal Reserves. This was especially true for the period of 2013-2018, when the values were more expressive, presenting a positive trend for regional environmental conservation. This research supports and highlights the effectiveness of environmental legislation, together with environmental enforcement, as responsible pressure factors in controlling deforestation and restoration of degraded areas of the State of São Paulo.
The environmental legislation fulfillment in implementation of legal reserves: an analysis for the central region of the state of São Paulo in the period 35 Years (1983 – 2018)
Keywords: Áreas legalmente protegidas; Cadastro ambiental rural; Código florestal; Legislação ambiental; Reserva legal; Rural environmental registry; Brazilian forest act; Environmental legislation; Legal reserve; CIENCIAS SOCIAIS APLICADAS::DEMOGRAFIA::DISTRIBUICAO ESPACIAL::DISTRIBUICAO ESPACIAL RURAL; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS